This other Eden : a novel - Harding, Paul, 1967- (W.W. Norton & Company, 2023)
"From the Pulitzer Prize-winning author of Tinkers, a novel inspired by the true story of Malaga Island, an isolated island off the coast of Maine that became one of the first racially integrated towns in the Northeast. In 1792, formerly enslaved Benjamin Honey and his Irish wife, Patience, discover an island where they can make a life together. Over a century later, the Honeys' descendants and a diverse group of neighbors are desperately poor, isolated, and often hungry, but nevertheless protected from the hostility awaiting them on the mainland. During the tumultuous summer of 1912, Matthew Diamond, a retired, idealistic but prejudiced schoolteacher-turned-missionary, disrupts the community's fragile balance through his efforts to educate its children. His presence attracts the attention of authorities on the mainland who, under the influence of the eugenics-thinking popular among progressives of the day, decide to forcibly evacuate the island, institutionalize its residents, and develop the island as a vacation destination. Beginning with a hurricane flood reminiscent of the story of Noah's Ark, the novel ends with yet another Ark. In prose of breathtaking beauty and power, Paul Harding brings to life an unforgettable cast of characters: Iris and Violet McDermott, sisters raising three orphaned Penobscot children; Theophilus and Candace Larks and their brood of vagabond children; the prophetic Zachary Hand to God Proverbs, a Civil War veteran who lives in a hollow tree; and more. A spellbinding story of resistance and survival, This Other Eden is an enduring testament to the struggle to preserve human dignity in the face of intolerance and injustice"--